The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/geosciences9050216
|View full text |Cite
|
Sign up to set email alerts
|

Automated Stone Detection on Side-Scan Sonar Mosaics Using Haar-Like Features

Abstract: Stony grounds form important habitats in the marine environment, especially for sessile benthic organisms. For the purpose of habitat demarcation and monitoring, knowledge of the position and abundance of individual stones is necessary. This is especially the case in areas with a scattered occurrence of stones in an environment which is otherwise characterized by relatively mobile sandy sediments. Exposed stones can be detected using side-scan sonar (SSS) data. However, apart from laborious manual identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The performance of the 0.25 m @ × 2 mosaic is affected most in the area with many small boulders, indicating that the super resolution fails to restore very small, clustered objects, a trend that is commonly observed in other areas of application [17]. On the other hand, and important for practical application, few false positives are introduced and the precision exceeds 0.85 for all natural facies, and a drop in performance depending on the background sediment, as observed in previous studies using Haar-like features for boulder detection [3], was not observed. However, in contrast to the good performance on natural seafloor, many false positives around plough marks created by anthropogenic impact exist, comprising a noticeable percentage of the total number of detections by the model between 2% and 4%, depending on the mosaic.…”
Section: Impact Of Seafloor Faciessupporting
confidence: 50%
See 1 more Smart Citation
“…The performance of the 0.25 m @ × 2 mosaic is affected most in the area with many small boulders, indicating that the super resolution fails to restore very small, clustered objects, a trend that is commonly observed in other areas of application [17]. On the other hand, and important for practical application, few false positives are introduced and the precision exceeds 0.85 for all natural facies, and a drop in performance depending on the background sediment, as observed in previous studies using Haar-like features for boulder detection [3], was not observed. However, in contrast to the good performance on natural seafloor, many false positives around plough marks created by anthropogenic impact exist, comprising a noticeable percentage of the total number of detections by the model between 2% and 4%, depending on the mosaic.…”
Section: Impact Of Seafloor Faciessupporting
confidence: 50%
“…The need for improving the resolution of images is widespread, including tasks in medical applications, object detection, or remote sensing [1]. In marine habitat mapping by acoustic remote sensing specifically, a recent topic of interest is the detection of individual boulders for purposes of hard ground delineation for marine spatial planning purposes as well as ecosystem research [2][3][4][5]. The detection of boulders is typically based on the interpretation of backscatter intensity mosaics derived from acoustic remote sensing by side scan sonars or multibeam echo sounders [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sawas et al [104] and Barngrover et al [105] have trained Haar-Like features (equivalent to convolutional neural networks with pre-selected kernel values) to automatically detect objects, specifically mines, using real and synthetic SSS images to increase the sample size. Applying Haar-Like features to the identification of stones based oñ 22,000 positive images and~340,000 negative samples, Michaelis et al [26] showed that training data in terms of different acoustic backscatter signals of the underlying seafloor have a strong influence on the detectability of stones in heterogeneous environments. Detection of mines using convolutional neural networks was attempted by Dzieciuch et al [106].…”
Section: Automated Stone Detectionmentioning
confidence: 99%
“…In times of highly sophisticated computer technology it is still common that experts manually interpret stone signatures on hydroacoustic backscatter data which is, however, very time-consuming and not practical for large and heterogeneous areas. Recently, research has focused on the automated identification of stone signatures in SSS backscatter data by means of machine learning techniques for selected study sites [21,26]. The future perspective is to improve publicly available training data sets to make the models more accurate and applicable for a variation of geological sites and large scale mapping campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…Those survey setups generate SSS image resolutions ranging from 0.25 m/pixel to 1 m/pixel, thus are insufficient to identify individual stones or boulders, especially in areas with coarse, mixed sediments [16]. Despite recent advances in methods for the automated detection of individual stones and boulders [27,28] methodological constraints of survey settings (acoustic frequencies, horizontal resolution and range, survey speeds, etc.) remain undiscussed.…”
Section: Introductionmentioning
confidence: 99%